Optimizing the expression of human dopamine receptors in escherichia coli - Boritzki, Vanessa; Hübner, Harald; Allikalt, Anni; Gmeiner, Peter; Wöhrl, Birgitta M. (International Journal of Molecular Sciences, 2021)
The human dopamine receptors D2S and D3 belong to the group of G protein-coupled receptors (GPCRs) and are important drug targets. Structural analyses and development of new receptor subtype specific drugs have been impeded by low expression yields or receptor instability. Fusing the T4 lysozyme into the intracellular loop 3 improves crystallization but complicates conformational studies. To circumvent these problems, we expressed the human D2S and D3 receptors in Escherichia coli using different N-and C-terminal fusion proteins and thermostabilizing mutations. We optimized expression times and used radioligand binding assays with whole cells and membrane homogenates to evaluate KD-values and the number of receptors in the cell membrane. We show that the presence but not the type of a C-terminal fusion protein is important. Bacteria expressing receptors capable of ligand binding can be selected using FACS analysis and a fluorescently labeled ligand. Improved receptor variants can thus be generated using error-prone PCR. Subsequent analysis of clones showed the distribution of mutations over the whole gene. Repeated cycles of PCR and FACS can be applied for selecting highly expressing receptor variants with high affinity ligand binding, which in the future can be used for analytical studies.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Expression in E. coli; FACS; Fluorescent ligand; Gene library; GPCR; Human dopamine receptors; Protein engineering; Radioligand binding